A qualitative interview study on successful pregnancies in women with spina bifida. Issue 1 (February 2022) - Tong, Ching Man Carmen; Dew, Morgan E.; Zimmerman, Kathrin D.; Hopson, Betsy D.; Blount, Jeffrey P.; Rocque, Brandon G.; Arynchyna, Anastasia; Wilson, Tracey; Joseph, David; Dangle, Pankaj; Powell, Danielle; McLain, Amie
Summary: Background: Improvements in antenatal medicine and surgical management for conditions associated with spina bifida such as hydrocephalus have extended the lifespan for individuals with spina bifida (SB) into adulthood. Decisions and education regarding reproductive care and pregnancies for patients with spina bifida are increasingly important. Pregnancy in these patients can be particularly challenging due to physical limitations, previous abdominal surgery for urinary or bowel management and presence of a ventriculoperitoneal shunt. To date, little research has examined the unique challenges that women with spina bifida face during pregnancy. Objective: The purpose of this descriptive study is to characterize the successful pregnancy histories of SB women and describe how pregnancy affected their mobility as well as bladder and bowel management. Study design: We conducted semi-structured interviews with women followed in our adult multidisciplinary SB clinic who previously had successful pregnancies. Questions regarding perinatal issues, obstetrical complications, urinary tract infections (UTI) and neurological changes were asked. Baseline mobility, bladder and bowel management were compared with changes during and after pregnancy. Results: 121 women of childbearing age were followed per year by our adult multidisciplinary spina bifida clinic between 2009 and 2016. We identified 6 women who successfully carried 8 pregnancies to term. There were no miscarriages. Four women had ventriculoperitoneal (VP) shunts. No children were born with neural tube defects. Mean age at first pregnancy was 23.5 years. Average gestational age at delivery was 37 weeks. 50% of the women had a spontaneous vaginal delivery. Five of six women intended to get pregnant; only one patient consumed folic acid regularly prior to pregnancy. Two of six women had bladder augmentation surgery, one of whom had urologic changes during pregnancy that persisted after childbirth. The other patient had a concomitant bladder neck sling procedure and did not have urologic issues during pregnancy. 50% of the patients experienced bladder-bowel dysfunction during their pregnancy. While 67% patients had full baseline ambulatory function, 4 patients had decreased mobility and required additional assistance during pregnancy. All returned to their baseline functionality afterwards. Conclusion: Six of our patients had eight successful pregnancies, with no children born with neural tube defects. New changes to mobility, bladder and bowel management were experienced by over half of the women during their pregnancies. Future studies should focus on the role of multidisciplinary teams in reproductive health education and perinatal management of changes to activities of daily living during pregnancy in this population. Summary Table Changes and complications during pregnancy. Summary Table Pregnancy characteristics Age at first pregnancy, mean 23.5 ± 3.7 Weeks of gestation, mean 37.2 ± 4.65 Number of pregnancies 1 4 (67%) 2 2 (33%) Prior lower urinary tract reconstruction 2 (33%) Bladder augmentation 2 (100%) Bladder neck sling 1 (50%) Ventriculoperitoneal shunt-related complications 0 (0%) Diagnosis of UTI 4 (67%) Worsened urinary incontinence 3 (50%) Worsened constipation 1 (17%) Decreased mobility 4 (67%) Pre-eclampsia 3 (50%) Mode of delivery C-section 3 (50%) Vaginal 3 (50%) Complications during delivery 1 (17%) Live births with neural tube defects 0 (0%)